FROST INVESTIGATION 1944-1945. COMPREHENSIVE REPORT. - ARCTIC CONSTRUCTION AND FROST EFFECTS LAB BOSTON MASS (1947)
The purpose of the report is to unify and summarize the results of observations and tests made at various airfields in the U. S. and reported in detail as appendices to this report, and to present the recommended design and evaluation criteria resulting from a study of the accumulated data. (Author) See also Rept. no. ACFEL-TR-7, AD-712 489, Rept. no. ACFEL-TR-24, AD-712 479 and Appendix 1, AD-712 382.